Optimum design of dynamic voltage restorer for voltage sag mitigation in distribution network - Deshpande V. Chinmay; Deshpande V. Chaitanya (Institute of Advanced Engineering and Science, 2019)
DVR is power electronic based device used for mitigation of voltage sag problem. In this paper, various inverter topologies such as Voltage source inverter, Z source inverter and Embedded Z source inverter are used and compared for operation of DVR. Here dual p-q theory is implemented as control technique which have excellent transient response and speed. Different inverter configurations are implemented for DVR and its simulation results are presented and compared. It has been observed that Embedded EZ source inverter topology is found to be effective. The Embedded EZ source inverter topology and its hardware results are presented and compared.